Antibodies from donor B cells perpetuate cutaneous chronic graft-versus-host disease in mice - Jin, Hua (Blood, 2016)
Cutaneous sclerosis is one of the most common clinical manifestations of chronic graft-versus-host disease (cGVHD). Donor CD4(+) T and B cells play important roles in cGVHD pathogenesis, but the role of antibodies from donor B cells remains unclear. In the current studies, we generated immunoglobulin (Ig)H(µγ1) DBA/2 mice whose B cells have normal antigen-presentation and regulatory functions but cannot secrete antibodies. With a murine cGVHD model using DBA/2 donors and BALB/c recipients, we have shown that wild-type (WT) grafts induce persistent cGVHD with damage in the thymus, peripheral lymphoid organs, and skin, as well as cutaneous T helper 17 cell (Th17) infiltration. In contrast, IgH(µγ1) grafts induced only transient cGVHD with little damage in the thymus or peripheral lymph organs or with little cutaneous Th17 infiltration. Injections of IgG-containing sera from cGVHD recipients given WT grafts but not IgG-deficient sera from recipients given IgH(µγ1) grafts led to deposition of IgG in the thymus and skin, with resulting damage in the thymus and peripheral lymph organs, cutaneous Th17 infiltration, and perpetuation of cGVHD in recipients given IgH(µγ1) grafts. These results indicate that donor B-cell antibodies augment cutaneous cGVHD in part by damaging the thymus and increasing tissue infiltration of pathogenic Th17 cells.